Moguća preventivna djelovanja kod korištenja suplemenata u sportskoj rekreaciji - Andrijašević, Mirna; Kalac, Vanja; Žnidarec Čučković, Ana; Vrbik, Andrea; Vrbik, Ivan (2018)
The main objective of this study was to determine the prevalence and frequency of use (not) allowed supplementation among recreational users and other forms of fitness and recreational content. Domestic and foreign literature clearly indicates the existence of (not) allowed supplementation in sports recreation. It should be noted that the problem of using illegal supplementation in sport, in most of the literature generally, considered in the context of doping in professional sports. Sports recreation area is on this issue largely ignored due to the lack of doping controls in the same extremely nontransparent terms. Therefore, the work is on the one hand aimed at the general empirical clarification of the use of (not) allowed agents among recreationists, while the other side wants to empirically examine their motives for use. These findings ultimately serve the development of preventive and educational guidelines aimed at reducing the use of illegal supplementation. As permitted use of supplementation ( nutritional supplements ) according to the latest research (e.g. Kläber 2010a , 2010b ) is often only the first stage on the way to the use of illegal supplementation ( doping ), it is necessary to analyze the use of illegal supplementation in sports and recreation including an analysis of the use of permitted supplementation. Therefore, this paper addresses the issue of how to use permissible and impermissible supplementation.
Bibliografske bilješke na kraju teksta ; bibliografija: 4 jed.
Abstract
Keywords: Sportska rekreacija -- Suplementacija -- Doping -- Nedozvoljena sredstva -- Dodaci prehrani -- Prevencija -- Edukacija